The effect of teacher career motivation on professional readiness to enter the teaching profession among indonesian pre-service teachers - Saiful Almujab Saiful; Veri Aryanto Sopiansah; Wiwin Lutfiah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examines the effect of teacher career motivation on professional readiness to enter the teaching profession among Indonesian pre-service teachers. The study was motivated by the paradox between the increasing number of teacher education students and the persistent shortage of teachers in Indonesia, indicating a possible gap between teacher education participation and professional readiness. Unlike previous studies that discuss teaching readiness in general terms, this study specifies readiness as professional readiness and situates the issue within the Indonesian teacher education context. A quantitative cross-sectional survey design was employed. The participants were 183 eighth-semester students from the Faculty of Teacher Training and Education at Universitas Pasundan, selected from a population of 339 students using stratified random sampling based on study programs. Data were collected through a structured questionnaire and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression. The results showed that students’ teacher career motivation was in the high category, and their professional readiness to enter the teaching profession was also high. Regression analysis indicated that teacher career motivation had a positive and significant predictive effect on professional readiness, B = 1.013, β = 0.859, t = 22.550, p < .001. The coefficient of determination showed that teacher career motivation explained 73.7% of the variance in professional readiness, R² = 0.737. These findings contribute to teacher education research by emphasizing motivation as a psychological resource that supports professional readiness. Practically, Indonesian teacher education institutions should strengthen reflective teaching practice, career guidance, mentoring, and professional identity development to enhance pre-service teachers’ motivation and readiness to enter the teaching profession.